The New Service Proletariat - Antunes, Ricardo (Revista Internacional de Salarios Dignos, 2020)
In recent decades, the spread of information technology, industrial automation, and other innovations has inspired visions of a coming “postindustrial society of services,” in which the proletariat as it existed in earlier eras would effectively disappear. However, even a cursory survey of the reality of contemporary global labour markets belies this myth. The emergence of a new class of educated, salaried workers in high-tech fields is predicated on the increasing invisibility of workers employed in sectors and settings ranging from call centres and telemarketing to hotels and cleaning companies to retail, fast food, and care services. The great majority of these jobs are precarious in one way or another: seasonal, part-time, temporary, informal, or freelance, with little or no security or benefits.